An analysis of the formation of profiles of physical and chemical indicators discharge in the context of compliance with the environmental quality of the recipient river - Klymenko, Mykola; Romanchuk, Liudmyla; Biedunkova, Olha; Vozniuk, Nataliia; Likho, Olena (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. Rivne Nuclear Power Plant, located on the Styr River, releases return water into the river without pre-treatment. While radiological impacts are well controlled, non-radiological effects remain poorly studied. The purpose of this work was to assess the non-radiological influence of Rivne NPP’s ORCS discharges on the physicochemical quality of the river. The research object comprised additional return cooling waters from the Rivne NPP and water from the river in the discharge zone. The subject was the variation of physicochemical quality indicators and their compliance with operational, discharge, and environmental standards.Methods. In 2023, weekly sampling was performed for additional cooling water, return water from the ORCS, and Styr River water downstream of the discharge. Measured parameters included pH, temperature, dry residue, alkalinity, hardness, Cl⁻, SO₄²⁻, PO₄³⁻, Na⁺, K⁺, NO₃⁻, NO₂⁻, N–NH₃, SS, DO, COD, and BOD₅. Analyses were conducted according to standardized methods. The data were compared with operational standards, permissible concentrations in return water and maximum permissible concentrations (MPC) for the environment. The water quality of the river was assessed using the following indices: salinity (SC), trophic-saprobiological state (TSS), organic pollution (OPI), nutrient pollution (NPI), and eutrophication (EI). Statistical analysis included descriptive statistics, Pearson correlation, cluster analysis and principal component analysis (PCA) using JASP version 0.14.3.Results and Discussion. Return water parameters were stable and within discharge standards. Styr River water largely met ecological MACs, but sporadic exceedances occurred: pH up to 8.66 (above 8.5), COD up to 83.2 mgO₂/L (MAC = 50 mgO₂/L), ammonium nitrogen up to 2.13 mg/L (MAC = 0.5 mg/L), PO₄³⁻ up to 0.798 mg/L (MAC = 0.7 mg/L), and BOD₅ up to 3.87 mgO₂/L (MAC = 3 mgO₂/L). These deviations were observed both upstream and downstream of the discharge, suggesting non-local sources unrelated to NPP activity. PCA identified three principal components explaining 66.9% of variance: PC1 (39.2%) linked to temperature and mineralization (Cl⁻, SO₄²⁻, NO₃⁻, Na⁺, K⁺), PC2 (18.6%) related to pH, alkalinity, hardness, and dissolved oxygen, and PC3 (9.1%) defined by SO₄²⁻ and BOD₅. Positive correlations were found between temperature and nitrates, pH and ammonium, and negative correlations between COD and BOD₅ or SO₄²⁻ and BOD₅. Cluster analysis showed that SO₄²⁻, NO₃⁻ and N–NH₃ demonstrate the most consistent relationships between the return water and the Styr River. According to the integral indices (IC, ITS, OPI, NPI, EI), it was found that the river water is characterized by a high degree of purity in terms of salt composition (IC = 1.25), the absence of eutrophication (EI = 0.08) and a low level of organic pollution (OPI = 0.15), with a slight trophic-saprobic load (ITS = 3.25) and moderate nutrient pollution (NPI = 1.56).Conclusions. Rivne NPPs ORCS return water met permissible concentrations, indicating effective cooling and water treatment. Styr River water generally complied with ecological MACs, and rare exceedances were not linked to Rivne NPP. PCA and correlation analyses identified temperature and mineralization as the main drivers of variability. Overall water quality is good but requires preventive, continuous monitoring and improved water management to ensure long-term ecological stability and environmental safety.